circKCNQ5 promotes the proliferation of DNA-methyltransferase 3A R882 mutated acute myeloid leukemia cells by elevating high-mobility group box 1 expression - Yijian Chen; Xiaodan Zhu; Chuanming Lin; Rong Xu; Pengxiang Xu; Liuyan Xin; Lin Li; Liqun Zhang (Annals of Medicine)
Background Patients with acute myeloid leukemia (AML) harboring the DNA-methyltransferase 3 A (DNMT3A) R882 mutation (DR882MUT) usually have a high recurrence rate and poor prognosis. circKCNQ5 levels were aberrantly elevated in patients with AML according to the microarray platform. Therefore, the purpose of this study is to investigate the effect and mechanism of circKCNQ5 on DR882MUT AML cell proliferation.Methods A DR882MUT cell line model was established. circKCNQ5 expression in AML cells expressing wild-type DNMT3A (DNMT3A-WT) or DR882MUT was analyzed using RT-qPCR. The proliferation of DNMT3A-WT and DR882MUT AML cells after transfection was measured using a CCK-8 assay. High-mobility group box 1 (HMGB1) protein expression was assessed by western blotting. The regulatory mechanism of circKCNQ5 on HMGB1 expression was studied using RNA pull-down and co-immunoprecipitation assays.Results circKCNQ5 expression increased gradually in HS-5, DNMT3A-WT, and DR882MUT AML cells. circKCNQ5 overexpression facilitated the proliferation of DNMT3A-WT KG-1a and HL-60 cells, whereas circKCNQ5 silencing blocked DR882MUT KG-1a and HL-60 cell proliferation. CircKCNQ5 interacts with HMGB1 and enhanced HMGB1 protein levels by inhibiting HMGB1 ubiquitination. HMGB1 protein levels increased gradually in HS-5, DNMT3A-WT, and DR882MUT AML cells. Furthermore, circKCNQ5 overexpression elevated HMGB1 protein levels in DNMT3A-WT KG-1a and HL-60 cells, whereas circKCNQ5 silencing reduced HMGB1 protein levels in DR882MUT KG-1a and HL-60 cells. HMGB1 overexpression remarkably increased the proliferative ability of DR882MUT KG-1a and HL-60 cells and circKCNQ5 silencing.Conclusions These findings verified that circKCNQ5 promotes the proliferation of DR882MUT AML cells by increasing HMGB1 expression.